Adherence To Respiratory And Nonrespiratory Medication In Patients With COPD: Results Of The German COSYCONET Cohort - Königsdorfer, Norbert (Patient Prefer Adherence, 2019)
BACKGROUND: Adherence to COPD medication is often considered to be lower than in other chronic diseases. In view of the frequent comorbidities of COPD, the economic impact of nonadherence and the potential for adverse effects, a direct comparison between the adherence to respiratory and nonrespiratory medication in the same patients seems of particular interest. OBJECTIVES: We aimed to investigate the intake of respiratory and nonrespiratory medication in the same patients with COPD and frequent comorbidities. METHOD: Within the COPD cohort COSYCONET, we contacted 1042 patients, mailing them a list with all medication regarding all their diseases, asking for regular, irregular and non-intake. RESULTS: Valid responses were obtained in 707 patients covering a wide spectrum of drugs. Intake of LABA, LAMA or ICS was regular in 91.9% of patients, even higher for cardiovascular and antidiabetes medication but lower for hyperlipidemia and depression/anxiety medication. Regular intake of respiratory medication did not depend on GOLD groups A-D or grades 1–4, was highest in patients with concomitant cardiovascular disorders and was lowest for concomitant asthma. It was slightly larger for LAMA and LABA administered via combined compared to single inhalers, and lower when similar compounds were prescribed twice. Most differences did not reach statistical significance owing to the overall high adherence. CONCLUSION: Our results indicate a high adherence to respiratory medication in participants of a COPD cohort, especially in those with cardiovascular comorbidities. Compared to the lower adherence reported in the literature for COPD patients, our observations still suggest some room for improvement, possibly through disease management programs.